2016
DOI: 10.12968/bjom.2016.24.5.362
|View full text |Cite
|
Sign up to set email alerts
|

Student midwives' perspectives on efficacy of feedback after objective structured clinical examination

Abstract: Students' experience of feedback is considered an indicator of the efficacy of the assessment process. Negative experiences of feedback are unproductive in terms of the likelihood that students will act on and learn from assessment. To understand the impact of feedback on learning, this study explored the experiences of student midwives after receiving feedback following objective structured clinical examination (OSCE). Data were collected from second-year undergraduate student midwives who had recently comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…This is very important and agrees with the report of a previous study where majority of the students rated being able to understand a feedback as the most desired thing about a feedback (Hall et al, 2012). This finding in this study may be linked to the fact that majority of these students (89.36%) also found the feedback to be friendly, supporting the suggestion of Killingley and Dyson (2016) that students' experiences of feedback are the most important indicator of the effectiveness of the feedback process.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is very important and agrees with the report of a previous study where majority of the students rated being able to understand a feedback as the most desired thing about a feedback (Hall et al, 2012). This finding in this study may be linked to the fact that majority of these students (89.36%) also found the feedback to be friendly, supporting the suggestion of Killingley and Dyson (2016) that students' experiences of feedback are the most important indicator of the effectiveness of the feedback process.…”
Section: Discussionsupporting
confidence: 92%
“…Whether written or verbal, the important thing is that it should be individualized and this fact was corroborated by the report of Mulliner and Tucker (2015) that students preferred individualized verbal and written feedback. Pankonin and Myers (2017) and Killingley and Dyson (2016) noted that negative or offensive feedback will not only affect students' engagement with the feedback but will also affect their behaviour indirectly by decreasing their feeling of self-worth. The study revealed that only a small proportion of examiners (7.50%) reported that students had complained of receiving offensive feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, students' feedback is considered a good indicator about the efficiency of the assessment tool and useful in improvements. The feedback received supports the applicability of this method in assessing the performance of nursing students (24) . Accordingly, this study was conducted to determine the nursing students' evaluation and feedback about objective structure clinical examination in the field of gerontological nursing.…”
Section: Discussionsupporting
confidence: 53%